Do the available data permit clarification of the possible dependence of Palaeozoic brachiopod generic diversity dynamics on global sea-level changes? A viewpoint - Ruban, Dmitry A. (Geologos, 2014)
At a glance, progress in palaeontology and eustatic reconstructions in the past decade permits to prove or to disprove the possible dependence of Palaeozoic brachiopod generic diversity dynamics on global sea-level changes. However, the available diversity curve is of much lower resolution than the eustatic curve. This problem can be resolved by decreasing the resolution of the latter. The other restriction linked to the chronostratigraphical incompatibility of the available data allows to focus on the Middle Palaeozoic only. A series of mass extinctions and other biotic crises in the Silurian-Devonian does not allow to interpret correctly the results of direct comparison of the brachiopod generic diversity dynamics with global sea-level changes. With the available data, it is only possible to hypothesize that the eustatic control was not playing a major part in diversity dynamics of Middle Palaeozoic brachiopods. The resolution of the stratigraphic ranges of Palaeozoic brachiopods should be increased signifcantly, and these ranges should be plotted against the most up-to-date geologic time scale. Until this task will be achieved, it is impossible to judge about the existence of any dependence (either full or partial) of the Palaeozoic brachiopod diversity dynamics on global sea-level changes.